Social Media Advocacy for SDG 5 in the Middle East: Insights from Egypt, Tunisia, and Jordan - Laila El Baradei; Mohamed Kadry; Ghadeer Ahmed (Journal of Social Equity and Public Administration)
This article explores how government organizations in Egypt, Tunisia, and Jordan use Facebook (FB) to advocate for the United Nations Sustainable Development Goal 5 (SDG 5). Guided by the Dragonfly Advocacy Model for evaluating social media advocacy and using CrowdTangle for FB content analysis, researchers analyzed advocacy efforts over eight and a half years, nearly midway through the planned implementation timeframe of the SDGs. Findings show that the SDG 5 targets most advocated by all three countries were those for women’s empowerment, eliminating violence, ending child marriage, and Female Genital Mutilation (FGM). “Reproductive health,” “technology,” and “unpaid work”’ were among the lowest-mentioned terms. Videos, animation, and influencers were key factors contributing to the effectiveness of FB posts. Gender inequities identified in these Middle Eastern countries, like FGM, honor killings, and inheritance rights, stood in contrast with Western concerns about abortion rights, access to contraception, flexible work arrangements, and digital inclusion.